Intensification and Complexity in Teachers’ Narrated Worklives - Wiebe, Sean; MacDonald, Craig (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
Reflecting on a previous study of teachers’ narratives, this epistolary conversation follows ideas of intensification and complexity that emerged in the authors’ return to the narrative accounts. Their conversation highlights representations of teaching as a struggle for recognition, personal happiness, and security—all within a system of accountability. Of central concern is the concept of complicity and how it is related to the seduction of consent through which teachers encounter a discourse of professionalism. By way of countering a misrecognized professionalism, the authors suggest that teachers’ narrative writings can be a means of forming a critical stance.